Răspunsuri

2014-10-17T19:04:57+03:00

2(x²+y²+z²)-4(3x+4y+5z)+92=0  x²+y²+z²-6x-8y-10z+9+16+25-4=0 ⇒(x-3)²+(y-4)²+(z-5)²-4=0   a)  [(x-3)²-4] + (y-4)² + (z-5)² = 0 ⇒⇒⇒ (x-5)(x-1)+(y-4)²+(z-5)²=0 ⇒(x-5)(x-1)=0; (y-4)² =0; (z-5)²=0 ⇒  x-5=0  x1=5 ; x-1=0 x2=1   (y-4)² = 0 ⇒ y-4=0 y1=4   (z-5)² = 0 ⇒ z-5=0   z1=5

b) (x-3)² + (y-6)(y-2) +(z-5)² = 0   (x-3)² =0 ⇒ x-3=0 ⇒ x3=3   y-6=0 ⇒ y2=6    y-2=0 ⇒ y3=2     (z-5)²=0    ⇒   z-5=0   ⇒   z2=5             c) (x-3)² + (y-4)² + (z-7)(z-3) = 0 ⇒x4=3  y4=4  z3=7, z4=3

Ați pus un 2 in fata primei paranteze
2x^2 +2y^2 + 2z^2 = 2(x^2 + y^2 + z^2)